(untitled) (Journal of Applied Membrane Science & Technology, 2023)
The threat of antimicrobial resistance (AMR) to human health is predicted to become a significant infectious disease. Domestic sewage and wastewater treatment plants (WWTPs) are critical hotspots for controlling the spread of antibiotic resistant bacteria (ARB) and antimicrobial resistance genes (ARGs) in the environment. A wastewater treatment system is not necessarily designed to mitigate AMR problems in wastewater. Furthermore, the presence of ARB and ARGs for a long time in WWTPs is reported as a reservoir of intracellular and extracellular ARG through horizontal gene transfer. Based on the studies, the additional membrane filtration with either microfiltration (MF) or ultrafiltration (UF) can reduce ARB and ARGs effectively through the separation mechanism. However, there are still inconclusive results when comparing ARG removal efficiencies between MBR and conventional processes. Further studies are required to clarify the effect of water qualities and membrane fouling conditions on ARG removal.